(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Gene therapy holds significant promise for treating a wide range of genetic disorders by targeting the underlying genetic causes. This abstract reviews current research efforts and advancements in gene therapy, highlighting its potential applications in various genetic disorders such as inherited metabolic disorders, immuno-deficiencies, hemoglobinopathies, and neurological diseases. Key topics discussed include gene therapy strategies, vector design, delivery methods, clinical trials, and emerging technologies such as CRISPR-Cas9 gene editing. The abstract aims to provide a comprehensive overview of the state of gene therapy and its potential impact on the treatment of genetic disorders.